Formation of hierarchical InAs nanoring/GaAs nanowire heterostructures. - Paladugu, M; Zou, J; Guo, Y; Zhang, X; Joyce, H; Gao, Q; Tan, H; Jagadish, C; Kim, Y (2009)
(Figure Presented) Rings around the wire: Novel hierarchical heterostructures, assembled by radial deposition of InAs on GaAs nanowires with nonplanar side walls, result in the formation of InAs nanorings. The mechanism of formation of such structures, determined by transmission electron microscopy, involves the preferential nucleation of InAs at concave regions of the GaAs surface by capillarity effects. © 2009 Wiley-VCH Verlag GmbH and Co. KGaA.